Analysis of the Relationship Between the Implementation of the Clinical Pathway for NSTEMI Disease and Service Variance - Palupi Setyo Hapsari; Ratno Adrianto; Irfansyah Baharuddin Pakki (GLOBAL HEALTH SCIENCE GROUP, 2025)
This research was conducted to address the increasing number of NSTEMI (Non-ST Elevation Myocardial Infarction) cases, which represent a significant portion of heart attack patients (85%) according to the 2023 Ischemic Myocardial Infarction National Audit. The challenge for healthcare providers is to ensure optimal care for these patients. Clinical Pathways are structured guidelines designed to improve service quality, but despite a relatively high compliance rate (82%) for filling out Clinical Pathways at Taman Husada Bontang Hospital, there has been no clear analysis of how Clinical Pathway implementation benefits patient outcomes. Therefore, the study aims to evaluate the relationship between the implementation of Clinical Pathway and the quality of care provided to NSTEMI patients. The study aims to analyze the relationship between the implementation of the Clinical Pathway for NSTEMI patients and the quality of service at Taman Husada Bontang Hospital. Quantitative research method with a cross-sectional case study approach. The sample technique used is non-probability sampling; the number of samples is 50 Clinical Pathway forms from NSTEMI patients treated at the hospital during the 2022-2023 period. The Chi Square test on the service variance variable has a significant relationship with the implementation of Clinical Pathway, with a p value of 0.000 < 0.05, incomplete documentation resulting in a lack of information about the service variance provided with an OR value of 1.5. The conclusion is that the implementation of Clinical Pathway is significantly related to the quality of services, especially the variance of actions given to patients. To improve service quality, improvements are needed in documentation and regular evaluation of the implementation of the Clinical Pathway.